The Effect of Leverage and Cash Flow Operation on Stock Prices with Company Value as Moderation - Tambun, Sihar; Syahputra, Donny (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The impact of the leiveirage and cash flow opeiration on stock prices and the value of the company as moderation is the goal of this policy. This study also examines the impact of the leiveirgaei and cash flow opeiration on the stock price and the value of the company as a moderation. This research sample is one of 50 companies that are listed on the Indonesian EIfeik Exchange in 2021-2023 at the Food and Beverage and Information Technology Surveyor. The method of research is tested by path analysis, using stata software to test direct and indirect effects. The results of the study prove that the leiveiragei is not beirpeinginginfluence and neigative in the face of the stock price. Cash flow opeiration has a positive and significant impact on stock prices. The value of the company is not significant and significant in the face of the stock price. The value of the company is not able to moderate and negate the relationship between the leiveiragei and the stock price. The value of the company is able to positively and significantly moderate the relationship between cash flow operations and stock prices. The results of this research provide information about the price of the company's investment in the food and beverage industry and information technology that can help decision-makers in an effort to increase the company's stock price.